Computational design of a new palladium alloy with efficient hydrogen storage capacity and hydrogenation-dehydrogenation kinetics - Das, Pritam; Lee, Young-Su; Lee, Seung-Cheol; Bhattacharjee, Satadeep (Pergamon Press Ltd., 2023)
Hydrogen-based fuels demand high-density storage that can operate at ambient temper-atures. Pd and its alloys are the most studied metal hydrides for hydrogen fuel cell ap-plications. This study presented an alternative Pd alloy for hydrogen storage that can store and release hydrogen at room temperature. The surface of the most commonly studied Pd (110) was modified with Au and Rh such that the hydrogen adsorption energy was 0.49 eV and the release temperature was 365 K. Both values are quite close to the optimal values for the adsorption energy and release temperature of a hydrogen fuel cell in real use. We further show that the modified Pd (110) surface has significantly stronger oxygen evolution reaction (OER) catalytic properties than the pure Pd (110) surface.(c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.